Riqueza de fauna ribereña del río Luján - Guichón, M. Laura (2007)
Riparian environments are usually characterized by high biological diversity, however, habitat degradation results from intensive use of the bank and the water course, and exploitation of the surrounding land. The Luján River basin, located in East-central Argentina, shows two distinct geomorphologic portions: the Pampean and the Deltaic portions, which in turn can be subdivided based on physiographic and land use features. Our objective was to compare riparian wildlife richness among the three zones of the Pampean portion (upper, middle, and lower), and between the two zones of the Deltaic portion (protected and antropic). From March to October 1997, 82 transects were randomly placed along the banks of the Luján River. We surveyed the presence of coypus, capybara, and Neotropical river otter based on signs of activity, and the presence of water birds (non Passeriformes) based on direct observation. In the Pampean portion, the number of species per transect in the middle zone was significantly lower than in the upper and lower zones. The middle zone is characterized by a narrow alluvial plain associated with more intense use of the land and less availability of water and hydrophilic vegetation in the surrounding habitats than the other two zones. In the Deltaic portion, the protected zone showed a larger species richness than the antropic zone, where intense use of the river and modification of its bank can negatively affect wildlife.